(untitled) (CAHIERS MAGELLANES-NS, 2024)
Objectives: Tuberculosis is caused by the bacterium Mycobacterium tuberculosis. It is an infectious disease which affect the lungs adversely. There are several strains of Mycobacterium tuberculosis in India like MDR(Multi drug resistant TB) and XDR(extremely drug resistance TB).So, it is crucial to develop plant based new drugs. Methodology: Several medicinal plants have been used traditionally in India to treat some Respiratory diseases like Cold, Cough etc. In this study, The phytocompounds of a traditionally used medicinal plant Andrographis paniculata was extracted by GC-MS analysis. The effectiveness of these compounds was screened against the enzyme 3-dehydroquinate dehydratase of Mycobacterial shikimate pathway . Molecular docking study was done to identify the phytocompounds which have highest binding affinity with this enzyme. Later Drug-likeness of these phytocompounds was studied followed by ADMET analysis. Findings: The result of molecular docking showed that the compounds Andrographin has highest binding affinity with 3-dehydroquinate dehydratase. This compound has good drug-like properties and obeys Lipinski’s rule of five. Later ADMET analysis reported that this compound have good absorption range , good bioavailabity score and less toxicity. Novelty: By Molecular docking, one phytocompound Andrographin from Andrographis panicullata was identified which can inhibit the mycobacterial enzyme so that the pathogen can not synthesize aromatic amino acids through shikimate pathway and can not survive inside the host cell. So, this compound may be used as lead molecule for development of future anti-tuberculotic drug.